TRANSFORMAÇÕES NO MUNDO DO TRABALHO NA REGIÃO DO GRANDE ABC: UMA ANÁLISE COMPREENSIVA A PARTIR DO FILME PEÕES - Estanislau, Cristiano (2010)
With the advent of the industrial revolution, capitalism has taken an astonishing way never seen before in other places in the world of work, to feed a fast-paced production, consumption and accumulation. This new era based on mechanization and a new division of labor imposed on the worker by the principle of fragmentation that following the chronometer model of scientific management and the production line of "butcher shop", that shared the work force and employee multiplied the accumulation of employer. However, in the 1970s capitalism has undergone a structural crisis that would transform the world of work again. This new transformation of capital based on the globalization and neo liberal concepts in order to further profitability over the labor force reached the objectivity and subjectivity of class that makes a living from working the (un) re-regulate their rights and conquests. In the world of Brazilian work changes of the world capital had their impact in the 1990s shaking entire production regions as do of Grande ABC, with structural unemployment and the restructuring process. In 2002 the filmmaker Eduardo Coutinho filmed a documentary - Peões - with 21 workers who recount their origins, their participation in the movement in the decades of 1970-1980-1990 and the outcomes of their lives making a building of itself by speaks. Thus, Peões will is for this dissertation the great link that will analysis corpus.that allow an approach between science and art. The phenomenological method will be used to analyze the present narratives for the understanding of the division of the capitalist work. This one is transforming the world of the work and it s perversely reaching the work-live-class when breaking up its subjectivity, that is explicit objectively in the fragmentation of the intersubjective relation with the others, the objects and the world. By means of the application of this method for the understanding of these narratives it was possible to reach at the following synthesis: the men and women, of Peões, had lived and still live nowadays intensely between the tenuous line of the resistance and of the submission, of the aware and alienation, blunting and the anonymity in the public sphere. It shows the importance, still in our days, of the widening of the dialectical thinking between the logic of the capitalist accumulation versus the logic of the human being survival.